2013
DOI: 10.1002/jsfa.6333
|View full text |Cite
|
Sign up to set email alerts
|

By‐product from decoction process of Hibiscus sabdariffa L. calyces as a source of polyphenols and dietary fiber

Abstract: The decoction process extracted some soluble carbohydrates, ash and some extractable polyphenols. The DF content changed in the dried residues, which could be considered as high-DF materials with a high proportion of soluble DF (∼20% of total DF) and considerable antioxidant capacity. These by-products could be used as an antioxidant DF source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 41 publications
3
28
4
1
Order By: Relevance
“…TDF represented 6.15% of H. sabdariffa calyces powder. This value, which is less than that was reported for some cereals, oilseed, vegetables and fruit processing by-products and algae (Elleuch et al, 2011), is not in accordance with those reported by Sayergo-ayerdi et al (2012) for dried hibiscus calyces (369.6 ± 17.5-389.2 ± 12.8 g kg −1 dry basis).…”
Section: Proximate Composition and Antioxidant Activity Of Hibiscus Scontrasting
confidence: 73%
See 3 more Smart Citations
“…TDF represented 6.15% of H. sabdariffa calyces powder. This value, which is less than that was reported for some cereals, oilseed, vegetables and fruit processing by-products and algae (Elleuch et al, 2011), is not in accordance with those reported by Sayergo-ayerdi et al (2012) for dried hibiscus calyces (369.6 ± 17.5-389.2 ± 12.8 g kg −1 dry basis).…”
Section: Proximate Composition and Antioxidant Activity Of Hibiscus Scontrasting
confidence: 73%
“…The H. sabdariffa calyces powder had a low moisture content of 8.33 ± 0.17% similar to those of cereals and their commercial derivate (Sangronis and Rebolledo, 1993), but lower than those reported by Sayergo-ayerdi et al (2012) for dried red sorrel calyces. The ash content, TPC and TFC of the red sorrel calyces in the present study were 8.092 ± 0.081%, 32.893 ± 0.319, and 18.346 ± 0.322 g kg -1 dry matters, respectively.…”
Section: Proximate Composition and Antioxidant Activity Of Hibiscus Smentioning
confidence: 76%
See 2 more Smart Citations
“…The first are reputedly rich in anthocyanins and other phenolic compounds (and thus possess good colouring and antioxidant properties), while the latter have a high organic acid content, resulting in beverages with intense sourness, a sensory characteristic much appreciated by locals (Cisse, Dornier, Sakho, MarDiop, et al, 2009). Indeed, the colouring, flavouring and thickening properties of hibiscus calyces have been shown to derive largely from their distinctive phenolic, organic acid and pectin composition (Fernández-Arroyo et al, 2011;Ramírez-Rodrigues, Plaza, Azeredo, Balaban, & Marshall, 2011;Sáyago-Ayerdi, Velázquez-López, Montalvo-González, & Goñi, 2014).…”
Section: Introductionmentioning
confidence: 99%